2021
DOI: 10.1093/neuros/nyab111
|View full text |Cite
|
Sign up to set email alerts
|

Incidence, Characteristics and Outcomes of Large Vessel Stroke in COVID-19 Cohort: An International Multicenter Study

Abstract: BACKGROUND While there are reports of acute ischemic stroke (AIS) in coronavirus disease 2019 (COVID-19) patients, the overall incidence of AIS and clinical characteristics of large vessel occlusion (LVO) remain unclear. OBJECTIVE To attempt to establish incidence of AIS in COVID-19 patients in an international cohort. METHODS A cross-sectional retrospective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
30
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 23 publications
6
30
1
Order By: Relevance
“…14 15 We also did not document a decrease in acute stroke evaluation and treatment volumes. [15][16][17][18] These differences likely highlight the local The pandemic and neurointervention heterogeneity of COVID-19 epidemiology and that the impact of the pandemic is likely to differ accordingly. The major strength of our study is the detailed data captured on all consecutive patients evaluated for a possible acute stroke during the study period and the high proportion (approximately 80%) of EVT-treated patients for which 90-day outcomes were documented.…”
Section: Discussionmentioning
confidence: 99%
“…14 15 We also did not document a decrease in acute stroke evaluation and treatment volumes. [15][16][17][18] These differences likely highlight the local The pandemic and neurointervention heterogeneity of COVID-19 epidemiology and that the impact of the pandemic is likely to differ accordingly. The major strength of our study is the detailed data captured on all consecutive patients evaluated for a possible acute stroke during the study period and the high proportion (approximately 80%) of EVT-treated patients for which 90-day outcomes were documented.…”
Section: Discussionmentioning
confidence: 99%
“…61 This observation was validated by an analysis of 41,971 patients with acute ischemic stroke in the Get With The Guidelines-Stroke database, which found that patients with COVID-19 were more likely to have LVOs and more severe stroke, in addition to being younger. 62 The Black population seems to be disproportionately represented among patients with COVID-associated stroke in the United States; 62,63 this community has also been disproportionately affected by the pandemic on all fronts. Whilst few studies have reported the underlying etiologies of stroke in the setting of COVID-19 in any detail, two studies have suggested that cryptogenic etiologies may be more common in patients with ischemic stroke in the context of COVID-19 compared to stroke without COVID-19.…”
Section: Strokementioning
confidence: 99%
“…We thank authors 1 for their interest in our work, 2 and for raising important points about the etiopathogenesis of acute ischemic stroke (AIS) in COVID-19.…”
mentioning
confidence: 99%